2020
DOI: 10.3390/pathogens9070521
|View full text |Cite
|
Sign up to set email alerts
|

Variation Profile of the Orthotospovirus Genome

Abstract: Orthotospoviruses are plant-infecting members of the family Tospoviridae (order Bunyavirales), have a broad host range and are vectored by polyphagous thrips in a circulative-propagative manner. Because diverse hosts and vectors impose heterogeneous selection constraints on viral genomes, the evolutionary arms races between hosts and their pathogens might be manifested as selection for rapid changes in key genes. These observations suggest that orthotospoviruses contain key genetic components that rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 83 publications
1
15
0
Order By: Relevance
“…As NSs is involved in suppressing RNA silencing in both plants and thrips 32 , it is perhaps not surprising that different variants may be favored in plants versus thrips. Consistent with this, a recent analysis of genomic diversity among Orthotospoviruses showed that NSs contained the most codon sites under positive selection among protein coding genes 33 . In the glycoprotein G C , the amino acid variant E362D appears to be very strongly selected for in thrips but only observed at very low frequencies in plants (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…As NSs is involved in suppressing RNA silencing in both plants and thrips 32 , it is perhaps not surprising that different variants may be favored in plants versus thrips. Consistent with this, a recent analysis of genomic diversity among Orthotospoviruses showed that NSs contained the most codon sites under positive selection among protein coding genes 33 . In the glycoprotein G C , the amino acid variant E362D appears to be very strongly selected for in thrips but only observed at very low frequencies in plants (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Genomic variation, evolution, and adaptation of the viruses to distinct hosts are reconciled by the combinative effect of genetic factors in their genome and selection pressure imposed by the host [ 40 , 41 , 42 ]. Besides, different host species may play an essential role in the standing genetic variability of BGV populations [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the chronological mechanism of emergence for some mutational patterns (nucleotide and amino acid substitutions) over the virus genome is key for anti-viral defense. Recent studies based on computational analyses have allowed the identification of fractions of non-synonymous to synonymous substitutions to determine virus evolution (as diverging clades) [ 41 , 45 ]. Purifying selection diminishes the volume of non-synonymous substitutions before they arise or are fixed in the genome and favors the fixation of those involving adaptive benefits.…”
Section: Introductionmentioning
confidence: 99%
“…These events occur naturally during RNA replication (Sanjuán and Domingo-Calap, 2016). Genetic variation and selection favor accumulation of mutations in parts of the genome responsible for critical processes, such as host adaptation, vector transmission, entry into the cell, and suppression of antiviral defense (Obenauer et al, 2006;Nigam and Garcia-Ruiz, 2020). variación genómica del coronavirus y los vinculamos a pruebas de diagnóstico, vacunas y fármacos antivirales.…”
Section: The Virusmentioning
confidence: 99%